Effectiveness of health education with booklet media on knowledge in pharmacological management of hypertension in the Pajang health center working area - Safitri, Putri Bela Eka; Sudaryanto, Agus (Jurnal EduHealth, 2024)
Hypertension treatment management is an important action taken to prevent hypertension, but this is still often unknown by patients due to the lack of patient knowledge of good and correct hypertension treatment management, which has an impact on increasing the number of hypertension patients each year, for this reason, providing health education is needed to increase public knowledge about hypertension treatment management. The purpose of this study was to identify the effectiveness of health education with booklet media on knowledge in managing hypertension treatment in patients with hypertension. This type of research is quantitative with a quasi-experimental design with a non-randomized control group pretest-posttest design. The sample amounted to 46 people with diagnostic hypertension at the Pajang Health Center in Surakarta. The sampling technique uses accidental sampling. The intervention was carried out by making two groups selected based on predetermined criteria and then given a pretest to determine the initial condition, for the experimental group given treatment, namely health education with booklet media while the control group was not given treatment only given health education with explanation, after which a posttest was given to both groups. Knowledge about hypertension was measured using a knowledge questionnaire. Data were analyzed using the t-test. The results showed that there was a significant difference between the intervention group given health education using booklets and the control group given health education without using booklets (p<0.001). So it can be concluded that there is an effectiveness of health education with booklet media on knowledge in pharmacological management of hypertension at Pajang Health Center.